PENGARUH PENURUNAN NILAI GOODWILL (GOODWILL IMPAIRMENT) TERHADAP BIAYA EKUITAS (COST OF EQUITY) PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2020 – 2024 - Jesiana Puspita Arum; Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the effect of goodwill impairment on the cost of equity in companies listed on the Indonesia Stock Exchange (IDX) during the period of 2020–2024. The control variables examined include book-to-market ratio, leverage, firm size, and liquidity. The research employs multiple linear regression analysis to examine the relationship between these variables and the cost of equity, which is calculated using the Capital Asset Pricing Model (CAPM).The results indicate that goodwill impairment does not have a significant effect on the cost of equity, with a p-value greater than 0.05. In contrast, book-to-market ratio, firm size, and liquidity show a significant negative effect on the cost of equity, while leverage does not exhibit a significant impact. These findings suggest that fundamental company factors such as valuation, size, and liquidity play a more dominant role in determining the cost of equity compared to goodwill impairment.This research contributes to the understanding of how goodwill impairment and company fundamentals influence investor risk perception and capital costs in emerging markets. The implications of this study highlight the importance of financial transparency and effective risk management to maintain lower equity costs and enhance investor confidence in the Indonesian capital market.